THE EFFECT OF COLLABORATIVE STRATEGY TOWARD THE READING COMPREHENSION - Risma Rahajeng Lestari; Sherly Citra Putri; Zumrotul Ainiyah (Pimpinan Cabang Muhammadiyah Kramat Jati, 2021)
This research aimed to figure out whether CSR gives positive effect toward students’ ability in reading comprehension. This reserach design was quasi experimental research. The text with which chosen by the researchers was recount text. The sample of this research were students in English Department of Mayjen Sungkono University. The data of this research was reading test scores which were analyzed by using t-test. It was found that there was significant difference on students’ reading comprehension who were taught by using Collaborative Strategic Reading (CSR) and the students taught by using non Collaborative Strategy Reading (CSR). This study consisted of 4 meetings. Each meeting consisted of planning, execution, observation and reflection. The result of post test showed that the mean score of posttest higher in experiment than control group. When Null Hyphotesis H0 was accepted it meant there was no difference significant in reading comprehension between class taught by using collaborative reading strategy nor without using collaborative reading strategy. Based on the finding, it signed that Ha was accepted and H0 was refused.